2019
DOI: 10.1111/wej.12517
|View full text |Cite
|
Sign up to set email alerts
|

Seeking river restoration appraisal best practice: supporting wider national and international environmental goals

Abstract: With growing investment in river restoration, we increasingly need to justify costs by demonstrating success and wider benefits of measures. To aid practitioners, the UK River Restoration Centre has worked with experts to develop a practical monitoring guidance that links objectives to specific monitoring to demonstrate achievable outcomes. Feedback, however, via an online questionnaire highlighted the need to rationalise the guidance contents for a new growing audience, taking advantage of new developments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Our analyses indicate that improvements in habitat conditions can offset the negative ecological effects of coarser-scale environmental pressures; for example, a greater range of habitats can alleviate the ecological implications of hydrological extremes through providing refuges [74][75][76]. Such findings indicate the importance of applying a BACI approach to river restoration appraisals to place ecological responses within the context of catchment-wide processes and assess biological recovery trends over time relative to non-restored sites [7,30,64].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Our analyses indicate that improvements in habitat conditions can offset the negative ecological effects of coarser-scale environmental pressures; for example, a greater range of habitats can alleviate the ecological implications of hydrological extremes through providing refuges [74][75][76]. Such findings indicate the importance of applying a BACI approach to river restoration appraisals to place ecological responses within the context of catchment-wide processes and assess biological recovery trends over time relative to non-restored sites [7,30,64].…”
Section: Discussionmentioning
confidence: 69%
“…With logistical issues and limited financial resources available to undertake scientific assessment of restoration effectiveness, targeted appraisals or demonstration projects can be used to assess hydromorphological and ecological responses, which could in turn guide other restoration activities [29,30]. Barrier removal is a well-established restoration technique that aims to enhance longitudinal connectivity to restore natural processes [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Where ecological condition is taken into account measures are often limited to single processes or features, such as vegetation structure and continuity (de Sosa et al 2018). As such, the full complexity of ecosystems are rarely assessed (England et al 2019).…”
Section: Has Ecological Condition Improved?mentioning
confidence: 99%
“…Of these records, only 10% included any mention of monitoring (Bernhardt et al 2005), and little information was found related to the ecological effectiveness of restoration (Palmer et al 2007). Similarly, of more than 5,000 river restoration projects recorded in the UK National River Restoration Inventory (NRRI), only 21% of records indicated that follow-up monitoring and assessment of existing projects has been undertaken (England et al, 2019), and where monitoring had been undertaken, results were often inconsistent (Smith et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Of these records, only 10% included any mention of monitoring (Bernhardt et al, 2005), and little information was found related to the ecological effectiveness of restoration . Similarly, of more than 5,000 river restoration projects recorded in the UK National River Restoration Inventory (NRRI), only 21% of records indicated that follow-up monitoring and assessment of existing projects have been undertaken (England, Naura, Mant, & Skinner, 2019), and where monitoring had been undertaken, results were often inconsistent (Smith, Clifford, & Mant, 2014). Despite these limitations, Vaughan and Ormerod (2010) suggest there is considerable value in analysing large regional or national datasets as the size, geographic and temporal spread of the data, are likely to overcome many of the weaknesses associated with data quality.…”
mentioning
confidence: 99%